The Role of Accounting Information in the Sentiment-Price Relation - CHEN, Kun-chih (Institutional Knowledge at Singapore Management University, 2009)
This study reconciles inconsistent evidence on the sentiment-price relation in prior studies by explicitly considering the effects of sentiment on both investor judgments and risk preferences. Using the uncertainty in accounting information, I am able to disentangle these two effects of sentiment and investigate the causes of the variations in the sentiment-price relation. The results show that, under low uncertainty, the effect of sentiment on risk preferences dominates in the sentiment-price relation, such that a negative effect of sentiment on price is observed. In contrast, under high uncertainty, the effect is less negative and, in fact, becomes positive. This suggests that in cases of high information uncertainty, the effect of sentiment on judgments dominates in the sentiment-price relation.